(untitled) (Stato, Chiese e pluralismo confessionale, 2020)
Sommario: 1. Società democratica e simboli religiosi - 2. La delibera di Giunta e l’ordinanza del Tribunale. La delicata sovrapposizione delle esigenze di riconoscibilità e di identificazione - 3. La sentenza di secondo grado. Il primato assiologico della pubblica sicurezza - 4. Sicurezza percepita e insicurezza dei diritti - 5. Conclusioni. The ʻAnti-veilʼ Ruling of Lombardy Executive Committee and the New Paradigm of Public Security ABSTRACT: On 10 December 2015, Lombardy Executive Committee approved a ruling which forbids the access to some public facilities to people who wear types of clothing aimed at covering the face. This ruling, whose object is to prevent any dangers that could affect public security, risks to discriminate Muslim women who wear an integral veil for religious reasons. With a controversial judgement, the Milan Court of Appeal confirmed the legitimacy of the provision. Contrarily to the opinion of the Court, this essay aims at proving that the Regional ruling couldn’t effectively get through a proportionality test, given the excessive intensity of the prohibition. In addition, other doubts are risen by the meaning of public security expressed by the provision.